Causality of Economic Growth, Renewable Energy, and Environmental Degradation in Organization of Islamic Cooperation Countries - Adelia De Tsamara Khansa; Tika Widiastuti (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan mengetahui hubungan kausalitas antara konsumsi energi konvensional, pertumbuhan ekonom, emisi karbon dioksida, dan konsumsi energi terbarukan di 39 negara Organisasi Kerjasama Islam (OKI) periode 1992-2018. Metode yang diterapkan ialah uji kausalitas Dumitrescu-Hurlin (2012) yang memperbolehkan adanya heterogenitas dan cross-sectional dependence. Temuan dari penelitian ini ialah terdapat interdependensi antara konsumsi energi konvensional dengan pertumbuhan ekonomi, sedangkan konsumsi energi terbarukan dipengaruhi oleh pertumbuhan ekonomi sebagaimana teori RKC U-shaped. Pertumbuhan ekonomi menyebabkan emisi karbon dioksida sebagaimana teori EKC-Kuznets. Tidak ditemukannnya hubungan kausalitas antara konsumsi energi konvensional dan terbarukan dengan emisi karbon dioksida. Penerapan kebijakan konservasi dapat diterapkan dengan memperhatikan pertumbuhan ekonomi. Penelitian terdahulu, menguji hubungan kausalitas tanpa memperhatikan cross-sectional dependence dan tidak memisahkan antara konsumsi energi konvensional dengan energi terbarukan. Kata Kunci: Energi terbarukan, Degradasi Lingkungan, Kausalitas. ABSTRACT This research aims to find causality between conventional energy consumption, economic growth, carbon dioxide emissions, and renewable energy consumption in 39 countries of the Organization of Islamic Cooperation (OIC) from 1992 to 2018. The method used Dumitrescu-Hurlin Causality Test (2012) that allows heterogeneity and cross-sectional dependence. The outcome affirms that there is interdependency between conventional energy consumption and economic growth, but renewable energy consumption affected economic growth that confirms RKC U-Shaped theory. The impact of economic growth affects environmental degradation and carbon dioxide emissions which accept EKC-Kuznets theory. The neutral hypothesis confirmed between conventional and renewable energy consumption and carbon dioxide emissions. Conservation policy could be implemented by considering economic growth. The previous study tested causality relationship without considering cross-sectional dependence and differentiate between conventional and renewable energy consumption. Keywords: Renewable energy, Environmental Degradation, Causality. DAFTAR PUSTAKA Adams, S., & Nsiah, C. (2019). Reducing carbon dioxide emissions; Does renewable energy matter? Science of the Total Environment, 693(25), 1-9. https://doi.org/10.1016/j.scitotenv.2019.07.094 Alfarabi, M. A., Hidayat, M. S., & Rahmadi, S. (2014). Perubahan struktur ekonomi dan dampaknya terhadap kemiskinan di provinsi Jambi. Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 1(3), 171-178. https://doi.org/10.22437/ppd.v1i3.1551 Antonakakis, N., Chatziantoniou, I., & Filis, G. (2017). Energy consumption, CO2 emissions and economic growth: An ethical dilemma. Renewable dan Sustainable Energy Reviews, 68(P1), 808-824. Banday, U. J., & Aneja, R. (2018). Energy consumption, economic growth and CO2 emissions: evidence from G7 countries. World Journal of Science, Technology and Sustainable Development, 16(1), 22-39. https://doi.org/10.1108/WJSTSD-01-2018-0007 Banday, U. J., & Aneja, R. (2020). Renewable and non-renewable energy consumption, economic growth and carbon emission in BRICS: Evidence from bootstrap panel causality. International Journal of Energy Sector Management, 14(1), 248-260. Dumitrescu, E.-I., & Hurlin, C. (2012). Testing for Granger non causality in heterogeneous panels. Economic Modelling, 29(4), 1450-1460. EIA. (2021). Carbon dioxide emisssions coefficients. Retrieved from EIA: https://www.eia.gov/environment/emissions/co2_vol_mass.php Field, B. C., & Olewiler, N. D. (2015). Environmental economics. Toronto: MacGraw-Hill Ryerson. Grafström, J. (2018). Divergence of renewable energy intention efforts in Europe: An econometric analysis based on patent counts. Environmental Economics and Policy Studies, 20(4), 829-859. Grossman, G. M., & Krueger, A. B. (1991). Environmental impacts of a North American free-trade agreement. The quarterly journal of impacts, 110(2), 353-377. Huang, B.-N., Huang, M. J., & Yang, C. W. (2008). Causal relationship between energy consumption and GDP growth revisited: A dynamic panel data approach. Ecological Economics, 67(1), 41-54. Irijanto, T. T., Zaidi, M. A., Ismail, A. G., & Arshad, N. C. (2015). Al Ghazali's thoughts of economic growth theory, a contribution with system thinking. Scientific Journal of PPI-UKM, 2(5), 233-240. Jaelani, A., Firdaus, S., & Jumena, J. (2017). Renewable energy policy in Indonesia: The Quranic Scientific signals in Islamic economics perspective. International Journal of Energy Economics and Policy, 193-204. Kahouli, B. (2018). The causality link between energy electricity consumption, CO2 emissions, R&D stocks and economic growth in Mediterranean countries (MCs). Energy, 145, 388-399. Khan, S. H., & Akram, M. H. (2018). Renewable energy profile of OIC Countries. Pakistan: COMSTECH. Lopez, L., & Weber, S. (2017). Testing for granger causality in panel data. The Stata Journal, 17(4), 972-984. Lu, W.-C. (2017). Greenhouse gas emissions, energy consumption and economic growth: A panel cointegration analysis for 16 Asian countries. International Journal of environmental research and public health, 14(11), 14-36. Muhammad, A. A., Arshed, N., & Kousar, N. (2017). Renewable energy consumption and economic growth in member of OIC countries. European Online Journal of Natural and Social Science, 6(1), 111-129. Naf'an. (2014). Ekonomi makro tinjauan ekonomi syariah. Yogyakarta: Graha Ilmu. Pesaran, M. (2004). General diagnostic test for cross-sectional independence in panel. Journal of Econometrics, 68(1), 79-110. Pesaran, M. H. (2007). A simple panel unit root test in the presence of cross-section dependence. Journal of Applied Econometrics, 22(2), 265-312. Ranjan, A., Banday, U. J., Hasnat, T., & Koçoglu, M. (2017). Renewable and non renewable energy consumption and economic growth: Empirical evidence from panel error correction model. Jindal Journal of Business Research, 6(1), 1-10. Ritchie, H. (2021, May 5). What are the safest and cleanest sources of energy? Retrieved from https://ourworldindata.org/safest-sources-of-energy Saad, N. M., Kassim, S., & Hamiid, Z. (2016). Best practices of waqf: Experiences of Malaysia and Saudi Arabia. Journal of Islamic Economics Lariba, 2(2), 57-74. SESRIC. (2019). OIC environment report 2019. Ankara: SESRIC. ______. (2020). OIC economic outlook 2020. Ankara: SESRIC. Shafie, S., & Salim, R. A. (2014). Non renewable and renwable energy consumption and CO2 emissions in OECD countries: A comparative analysis. Energy Policy, 66, 547-556. Sharif, A., Raza, S. A., Ozturk, I., & Afshan, S. (2019). The dynamic relationship of renewable and nonrenewable energy consumption with carbon emission: A global study with the application of heterogeneous panel estimations. Renewable Energy, 133, 685-691. Tietenberg, T., & Lewis, L. (2018). Environmental & natural resource economics. New Jersey: Pearson Education. Toumi, S., & Toumi, H. (2019). Asymmetric causality among renewable energy consumption, CO2 emissions, and economic growth in KSA: Evidence from a non-linear ARDL model. Environmental Science and Pollution Research, 26(5), 16145-16156. Tugcu, C. T., & Topcu, M. (2018). Total, renewable and non renewable energy consumption and economic growth: Revisiting the issue with an asymmetric point of view. Energy, 152(C), 64-74. Tuna, G., & Tuna, V. E. (2019). The asymmetric causal relationship between renewable and non-renewable energy consumption and economic growth in the ASEAN-5 countries. Resources Policy, 62, 114-124. WaCIDS. (2021, August 23). Green waqf: Wakaf sebagai solusi perbaikan alam dan kemandirian energi. Retrieved from https://wacids.or.id/2021/08/23/green-waqf-sebagai-solusi-perbaikan-alam-dan-kemandirian-energi/ WHO. (2018). COP24 special report health & climate change. Geneva: WHO. World Bank. (2019). Economy. Retrieved from https://datatopics.worldbank.org/world-development-indicator/themes/economy.html World Bank. (2021). State and trends carbon pricing 2021. Washington DC: World Bank. Yamane, T. (1967). Statistics: An introductory analysis. New York: Harper anda Row. Yao, S., Zhang, S., & Zhang, X. (2019). Renewable energy, carbon emission and economic growth: A revised environmental Kuznets Curve perspective. Journal of Cleaner Production, 1338-1352. Zaidi, S. A., Danish, Hou, F., & Mirza, F. M. (2018). The role of renewable and non-renewable energy consumption in CO2 emissions: a disaggregate analysis of Pakistan. Environmental Science and Pollution Research, 25(31, 31616-31629.